Análisis de QGIS cómo plataforma tecnológica de soporte al procesamiento de datos geográficos relacionados con la agricultura en el cantón Puebloviejo. - Moncayo Barahona, Emily Lisseth (2023)
Geographic Information Systems (GIS) are essential tools for spatial management in various industries, including agriculture. In particular, the open source software Quantum GIS (QGIS) can be a very useful tool for farmers in Puebloviejo, a major canton in Ecuador with an economy based on agriculture. QGIS can help farmers analyze soil and terrain data to determine which types of crops are most suitable for a certain area, as well as monitor crop growth and detect problems early. It can also help farmers plan and optimize land use and crop rotation, analyze resource distribution, and prevent natural hazards such as floods, landslides, and droughts. The implementation of QGIS in Puebloviejo could significantly contribute to the development and improvement of agricultural activity in the region. By using QGIS, you can identify land use patterns, areas with the greatest agricultural potential, and perform agricultural productivity analysis. In addition, risk areas in terms of natural disasters can be identified and preventive measures taken to mitigate the effects of possible disasters on agricultural activity. The integration of geospatial databases and GIS is essential for the effective management of geographic information and decision making in various industries that could effectively benefit the planning and growth of this area. The integration of both systems involves transferring data between them and visualizing and analyzing data in an integrated way, using technologies and techniques that include interoperability, standardization and intuitive user interfaces. In summary, the use of QGIS in the analysis of geographic data related to agriculture in Puebloviejo can help farmers make informed decisions regarding crop management and the use of natural resources, optimizing land use, improving the productivity and efficiency, and mitigating the effects of possible natural disasters on agricultural activity. The integration of geospatial databases and GIS is essential for the effective management of geographic information and decision making in various industries.